PROSES IMPLEMENTASI STRATEGI NABITEPI MENEMBAK SENJATA RINGAN DI SEKOLAH CALON TAMTAMA RINDAM XII/TANJUNGPURA - Saripudin, Didin; Astuti, Indri; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractShooting is a basic ability that must be owned by every soldier of TNI AD in order to win the battle. Education is seen as a main factor which determines the growth of human resource capacity as well as the growth in all fields, that is through educated performance improvements. This research based on the assumption which the implementation of Nabitepi’s Strategy in shooting light weapons can produce professional soldiers in the field of shooting. This is supported by the following research results: Nabitepi’s design strategy coaches in basic learning to shoot light weapons in the school Tamtama Rindam XII/Tpr in three types of activities namely Nabitepi Strategy implementation design in the field/practice/training, and design of field activities. The implementation of the stategy of Nabitepi in the lesson of shooting light weapons affect the students' motivation of 47.5%. As for the influence of the implementation of the Strategy of Naitepi and the student motivation towards the capability to shoot light weapons simultaneously amounted to 88.6%. Meanwhile, the influence of the implementation of the strategy of Nabitepi towards the capability to shoot light weapons of students separately is 17.6%. Key Words: The Implementation, Nabitepi Strategy, Weapons, Tamtama Candidates